Dániel Győri was Born 100 years ago Former Professor of Soil Science at Georgikon - Lehoczky, Éva; Matusné Sényi, Klára; Pálmai, Ottó (GEORGIKON FOR AGRICULTURE, 2024)
Professor Dániel Győri is a leading figure in Hungarian soil science education and research, and a former head of the Department of Soil Science at the Georgikon Campus of the Hungarian University of Agricultural and Life Sciences. He was born on 1 June 1924 to a family of farmers in Kosd, where he was awarded the title of Honorary Citizen in 2009. He began his secondary school education in 1943 as a private student at the Lónyay Street Grammar School of the Hungarian Reformed Church in Budapest, where he completed eight grades in five years and graduated in 1948. In the same year, he would be admitted to the Eötvös Lóránd University of Sciences as a student of chemistry, where he graduated with excellent results in 1952. After winning the tender for teaching soil science at the Agricultural College of Keszthely, he started teaching on 1 February 1964. He was commissioned to organise an independent Department of Soil Science, and after this he was appointed Head of Department and held this post until 1989, for 25 years. He has received numerous awards in recognition of his professional work. Professor Dániel Győri has been a dedicated teacher of soil science to generations of professionals, and a committed scientific researcher. He is with love remembered by his colleagues, students, friends and admirers.
Keywords: Dániel Győri; education; micronutrients; soil fertility; Keszthely – Hungary